Ensuring the Rights of Vietnamese Migrant Workers in the Context of the Covid - 19 Pandemic - Nguyen Thi Hong Yen; Tran Thi Thu Thuy (Journal of Contemporary Sociological Issues, 2022)
Broke out since December of 2019, the COVID-19 pandemic has become a global challenge that seriously affected the development of various economies in the world, including Vietnam. According to the Ministry of labour, War Invalids and Social Affairs of Vietnam (MOLISA), more than 5,000 migrant workers have to return home and risk losing their jobs and income. In addition, the migrant workers who still stay abroad are also subject to myriad difficulties in their lives and health situation, underemployment and reduced income, discrimination, prejudice and xenophobia etc. To clarify the legal and practices issues regarding protecting the rights of Vietnamese migrant workers in the context of COVID-19, the article focuses on analyzing (i) the status of Vietnamese migrant workers and the impacts of the Covid-19 pandemic on this group; (ii) the regulations of Vietnam related to the rights of migrant workers; (iii) the policies have been adopted by the Vietnamese Government to protect the rights of Vietnamese migrant workers during the pandemic, and (iv) recommendations for implementation of policies and laws to ensure the rights of Vietnamese migrant workers in similar circumstances. Keywords: Human Rights, Migrant’s Rights, Covid-19 Pandemic, Vietnamese Migrant Worker, Labourer’s Rights.